Back Cover: A Synthetic Toolbox for the In Situ Formation of Functionalized Homo‐ and Heteropolysaccharide‐Based Hydrogel Libraries (Chem. Eur. J. 52/2016). Issue 52 (16th November 2016) - Dibbert, Nick; Krause, Andreas; Rios‐Camacho, Julio‐Cesar; Gruh, Ina; Kirschning, Andreas; Dräger, Gerald
Abstract : A synthetic toolbox for chemical craftsmen is presented for constructing libraries of differently functionalized polysaccharides and "click products" derived therefrom. These tools are useful for hydrogel formation suited for biomedical research. The picture illustrates the chemical toolbox and the procedure for the formation of new polysaccharide‐based biocompatible hydrogels. More information can be found in the Full Paper by A. Kirschning, G. Dräger et al. onpage 18777 ff.